Enhanced energy density quasi-solid-state supercapacitor based on an ionic liquid incorporated aqueous gel polymer electrolyte with a redox-additive trimethyl sulfoxonium iodide. (1st August 2023) - Hor, Abbas Ali; Yadav, Neetu; Hashmi, S.A.
Abstract: Enhancing interfacial redox activities by introducing a redox-active species in electrolytes is a latest strategy to enhance the performance characteristics of supercapacitors. Herein, an aqueous redox-active gel polymer electrolyte (R-GPE) is synthesized by adding a redox-active salt (trimethyl-sulfoxonium iodide, TMSI) in an ionic liquid (1-ethyl-3-methylimidazolium chloride, EMICl), entrapping in a host polymer poly(vinyl alcohol). The free-standing film of R-GPE shows high flexibility and excellent electrochemical properties including high room temperature ionic conductivity (σRT  = 15.4 mS cm −1 ) and wide electrochemical stability window (ESW ~ 2.9 V versus Ag/Ag + ), which makes the R-GPE film suitable in supercapacitor application. Two supercapacitors are fabricated using gel polymer electrolytes (without and with TMSI, respectively), and activated carbon electrodes, produced from a bio-waste pollen-cone. Presence of TMSI as redox-additive in R-GPE enhances the performance of the device with almost 5-times higher value of specific capacitance (~613 F g −1 ) and specific energy (~69 Wh kg −1 ) as compared to the device with GPE (without TMSI). The supercapacitor cell with R-GPE demonstrates a moderate rate capability. The device offers a ~60 % (i.e. ~357 F g −1 ) capacitance retention after ~5000 charge-discharge cycles with initial fading of ~18 % and >95 % of Coulombic efficiency. Graphical abstract: Unlabelled Image Highlights: A new additive TMSI used to synthesize redox-active gel polymer electrolyte R-GPE Flexible R-GPE film with high ionic conductivity found suitable for supercapacitor Carbon supercapacitor with redox-active GPE film shows high capacitance ~613 F g −1 . Redox-active species are responsible for significant enhancement in energy density. Supercapacitor shows reasonable performance for 5000 charge-discharge cycles.